Cryoablation combined with programmed cell death protein 1 (PD-1) inhibitors regulates myeloid-derived suppressor cells (MDSCs) through the JAK2-STAT3-S100A8/A9 axis in mice with Lewis lung carcinoma - Jiao Li; Xiaoyu Zhao; Man Qi; Xuxin Chen; Wei Chen; Shuo Zhang; Zhouli Tan; Chunyang Zhang; Zhihai Han (International Journal of Hyperthermia, 2025)
Background Cryoablation (Cryo) can enhance the efficacy of tumor immunotherapy, and the synergistic effect of Cryo with immune checkpoint inhibitors has been demonstrated in some tumor models. Because myeloid-derived suppressor cells (MDSCs) accumulate in lung cancer patients and promote tumor progression, lung cancer can be treated by targeting MDSCs. At present, the effect and mechanism of action of combination Cryo + programmed cell death protein 1(PD-1) inhibitors on MDSCs in cancer patients are unclear.Methods A mouse model of Lewis lung carcinoma (LLC) with bilateral tumor-bearing was established and mice were treated with Cryo, PD-1 inhibitor, or Cryo + PD-1 inhibitor (combination therapy). Subsequently, the growth trend of right-side (distant) tumors was determined. The expression of apoptosis-related proteins was detected by western blot assay, and flow cytometry was used to analyze the percentages of MDSCs and CD8+ T cells. QRT-PCR and western blot were used to detect the levels of effector molecules related to the immunosuppressive function of MDSCs and signaling pathways.Results Cryo + PD-1 inhibitor significantly inhibited the growth of right-side untreated tumors and promoted tumor cell apoptosis in LLC mice. Combined therapy reduced the proportion of MDSCs in the tumor microenvironment and peripheral blood of tumor-bearing mice, promoted MDSCs maturation, and increased the proportion of CD8 + T cells. The combination therapy also decreased the level of effector molecules related to the immunosuppressive function of MDSCs and down-regulated the JAK2-STAT3-S100A8/A9 axis in MDSCs.Conclusions Cryo + PD-1 inhibitor treatment can significantly delay tumor growth in mice and inhibit the proliferation and function of MDSCs through the JAK2-STAT3-S100A8/A9 axis, thereby improving the immunosuppressive tumor microenvironment.